Transparent polycarbonate coated with CeO2 nanozymes repel Pseudomonas aeruginosa PA14 biofilms. Issue 1 (13th December 2021) - Jegel, Olga; Pfitzner, Felix; Gazanis, Athanasios; Oberländer, Jennifer; Pütz, Eva; Lange, Martin; von der Au, Marcus; Meermann, Björn; Mailänder, Volker; Klasen, Alexander; Heermann, Ralf; Tremel, Wolfgang
Abstract : CeO2 /polycarbonate nanocomposites are highly transparent and bacteria repellent. Abstract : Highly transparent CeO2 /polycarbonate surfaces were fabricated that prevent adhesion, proliferation, and the spread of bacteria. CeO2 nanoparticles with diameters of 10–15 nm and lengths of 100–200 nm for this application were prepared by oxidizing aqueous dispersions of Ce(OH)3 with H2 O2 in the presence of nitrilotriacetic acid (NTA) as the capping agent. The surface-functionalized water-dispersible CeO2 nanorods showed high catalytic activity in the halogenation reactions, which makes them highly efficient functional mimics of haloperoxidases. These enzymes are used in nature to prevent the formation of biofilms through the halogenation of signaling compounds that interfere with bacterial cell–cell communication ("quorum sensing"). Bacteria-repellent CeO2 /polycarbonate plates were prepared by dip-coating plasma-treated polycarbonate plates in aqueous CeO2 particle dispersions. The quasi-enzymatic activity of the CeO2 coating was demonstrated using phenol red enzyme assays. The monolayer coating of CeO2 nanorods (1.6 μg cm −2 ) and the bacteria repellent properties were demonstrated by atomic force microscopy, biofilm assays, and fluorescence measurements. The engineered polymer surfaces have the ability to repel biofilms as green antimicrobials on plastics, where H2 O2 is present in humid environments such as automotive parts, greenhouses, or plastic containers for rainwater.